Taste of Macau : Portuguese Cuisine on the China Coast - Jackson, Annabel (Book collections on Project MUSE., 2003)
Over 450 years ago, the Portuguese landed in what was to be the first European colony in Asia, Macau, bringing their culture and their cuisine. This lavishly illustrated cookbook is the first to introduce to the English-speaking world one of the oldest 'fusion' cuisines in Asia. It includes 62 recipes, most of which are straight from the source - old family recipe collections or the files of influential Macanese chefs.